Security and illegality in Cuba's transition to democracy - Romero, Vidal (Woodbridge : Tamesis, 2021)
How can an environment be created in Cuba in which safety is not sacrificed for more open markets and politics?
Title from publisher's bibliographic system (viewed on 11 Jun 2021).
Keywords: National security -- Cuba; Crime forecasting -- Cuba; Crime -- Political aspects -- Cuba; Democracy -- Cuba